2019
DOI: 10.1021/acs.jced.9b00162
|View full text |Cite
|
Sign up to set email alerts
|

Stable Phase Equilibrium of the Quaternary System Li2SO4 + Cs2SO4 + MgSO4 + H2O at 298.2 K

Abstract: To understand the thermodynamic characteristics of the brine located in Qaidam Basin salt lake, the stable equilibrium solubilities, densities, and refractive indices in the quaternary system Li2SO4 + Cs2SO4 + MgSO4 + H2O were studied at T = 298.2 K using the isothermal dissolution method. Chemical analysis and X-ray diffraction (XRD) were applied to determine the crystalloid forms of the solid phases. In this aqueous equilibrium system at 298.2 K, two double salts (3Li2SO4·Cs2SO4·2H2O and Li2SO4·Cs2SO4) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Regarding the thermodynamic equilibrium studies, a train of water−salt systems containing elemental lithium or magnesium has been studied, such as the system Li + , Na + , Mg 2+ //SO 4 2− −H 2 O at 293.15 K, 9 298 K, 10 and 348 K. 10 The system Li + , Na + , Mg 2+ //SO 4 2− −H 2 O at 263 K 11 and ternary system (Rb + ) Mg 2+ , Cs + //SO 4 2− −H 2 O at 298.2 K 12 use Pitzer's model to give a theoretical calculation phase diagram. The salts Na 2 SO 4 •10H 2 O and Na 2 SO 4 were found in the system Na + , Cs + //SO 4 2− −H 2 O at 298.2 K. 13 It has been found in systems Li + , Na + , Cs + //SO 15 that lithium and cesium are difficult to separate directly from brine by the evaporation and crystallization method. Although quaternary system Li + , Na + , Mg 2+ // SO 4 2− −H 2 O has been studied using the isothermal dissolution method or isothermal evaporation method at different temperatures, 9−11 the stable phase equilibrium of the system at 323 K has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the thermodynamic equilibrium studies, a train of water−salt systems containing elemental lithium or magnesium has been studied, such as the system Li + , Na + , Mg 2+ //SO 4 2− −H 2 O at 293.15 K, 9 298 K, 10 and 348 K. 10 The system Li + , Na + , Mg 2+ //SO 4 2− −H 2 O at 263 K 11 and ternary system (Rb + ) Mg 2+ , Cs + //SO 4 2− −H 2 O at 298.2 K 12 use Pitzer's model to give a theoretical calculation phase diagram. The salts Na 2 SO 4 •10H 2 O and Na 2 SO 4 were found in the system Na + , Cs + //SO 4 2− −H 2 O at 298.2 K. 13 It has been found in systems Li + , Na + , Cs + //SO 15 that lithium and cesium are difficult to separate directly from brine by the evaporation and crystallization method. Although quaternary system Li + , Na + , Mg 2+ // SO 4 2− −H 2 O has been studied using the isothermal dissolution method or isothermal evaporation method at different temperatures, 9−11 the stable phase equilibrium of the system at 323 K has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…The ternary system Li + , Mg 2+ //SO 4 2– –H 2 O at 273.2, 288.15, 298.2, and 308.15 K demonstrated that a simple system is likely been formed rather than a double system. The research on the phase equilibrium of the ternary system Li + , Rb + //SO 4 2– –H 2 O 298 K has been reported in many articles in the 20th century. Some scholars have studied the quaternary systems Li + , K + , Rb + //SO 4 2– –H 2 O, Li + , Na + , Rb + //SO 4 2– –H 2 O. Our research group has also completed the following research work: ternary system Li + , Rb + //SO 4 2– –H 2 O at 298.2 K, Rb + , Mg 2+ //SO 4 2– –H 2 O at 298.2 K, , quaternary system Rb + , Cs + , Mg 2+ //SO 4 2– –H 2 O at 298.2 K, and Li + , Cs + , Mg 2+ //SO 4 2– –H 2 O at 298.2 K. , Owing to the low annual average temperature­(near 0 degrees) in the Qaidam Basin, it is necessary to determine a stable phase equilibrium of the sulfate system with lithium, rubidium, and magnesium coexistence at 273.2 K, which has not been reported yet. The isothermal dissolution method was used in this work to carry out a study on the phase equilibrium of the quaternary system Li + , Rb + , Mg 2+ //SO 4 2– –H 2 O at 273.2 K. It provides solubility data for the separation and extraction of lithium and rubidium resources in brine.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, there is a larger crystallization area for these double salts in the corresponding system. With the increase of temperature, the systems (Li + , Cs + , Mg 2+ //SO 4 2– –H 2 O) and (Li + , Na + , Cs + //SO 4 2– –H 2 O) form the double salts Li 2 SO 4 ·Cs 2 SO 4 and 3Li 2 SO 4 ·Cs 2 SO 4 ·2H 2 O at 298.2 K, making it impossible to extract the pure salt lithium sulfate from the system directly. Perhaps lithium can be isolated and purified after precipitation from brine in the form of lithium double salt.…”
Section: Introductionmentioning
confidence: 99%